1968
DOI: 10.1037/h0026491
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of learning from a programmed text compared with a conventional text covering the same material.

Abstract: Studying a programmed textbook was compared with studying a conventional textbook to determine which method leads to better performance on a content examination. Both texts covered similar material on operant psychology. In a setting where 12 teaching assistants each taught 2 discussion sections with enrollments of about 22 students, 1 section studied the programmed text, and the other studied the conventional text. At the end of the semester, all students took an examination which contained several types of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…These findings suggested that as students could bring their prior learning to bear on the task, i.e., when the task relied more on previously learned material, there were no differences between different response modes. Daniel and Murdoch's (1968) study also supports a familiarity interpretation. These investigators found that a group studying Holland and Skinner's (1961) program on operant psychology achieved more than a group studying the same subject matter using Skinner's non-programmed writings.…”
Section: Research Findingssupporting
confidence: 80%
See 1 more Smart Citation
“…These findings suggested that as students could bring their prior learning to bear on the task, i.e., when the task relied more on previously learned material, there were no differences between different response modes. Daniel and Murdoch's (1968) study also supports a familiarity interpretation. These investigators found that a group studying Holland and Skinner's (1961) program on operant psychology achieved more than a group studying the same subject matter using Skinner's non-programmed writings.…”
Section: Research Findingssupporting
confidence: 80%
“…Specifically, Karis et al (1968) found that the superiority of CR disappears when synonyms and paraphrasing of technical medical terminology are scored as acceptable on the posttest. Similarly, Daniel and Murdoch (1968) demonstrated that the superiority of CR hinged upon a test requiring students to respond with technical, presumably novel, terms. The fact that the advantage of CR disappeared in these studies when technical and presumably unfamiliar responses were removed as a variable strongly supports a familiarity interpretation and can not directly be accounted for by an explanation dealing with the blackout ratio.…”
Section: Cñ Familiarity and Blackout Ratiomentioning
confidence: 99%
“…This familiarity interpretation is in accord with the results of Daniel and Murdoch (1968) who found overall achievement differences favoring a group studying operant psychology with a constructed response program (Holland & Skinner, 1961) compared to subjects studying the same subject with nonprogrammed writings. When differences between the groups on the most technical, and presumably least familiar, subtest were eliminated from the dependent measures by covariance adjustment the other group differences were no longer significant.…”
supporting
confidence: 86%
“…much research has suggested that programmed instruction is superior to conventional teaching practices in promoting learning (Chatterjee & Basu, 1987;daniel & murdoch, 1968;Fernald & Jordan, 1991;Kulik, Cohen, & Ebeling, 1980). Conversely, other studies have indicated that it produces similar (Kulik, schwalb, & Kulik, 1982) or inferior (Bhushan & sharma, 1975) learning when compared to traditional approaches.…”
mentioning
confidence: 96%